Developmental neurobiology / Marcus Jacobson, Mahendra S Rao - Jacobson, Marcus
With its comprehensive and completely updated coverage, generous illustrations, and a table of contents that reads like a Who's Who in neuroscience, this new and expanded Fourth Edition is a must book for the professional neurobiologist and others seeking definitive and authoritative information in this important field. Instructors, as well as graduate and advanced under-graduate students, will also appreciate its clearly presented information, historical references, and organization for classroom use.